On Exponential Stabilizability for a Class of Switched Nonlinear Systems with Mixed Time-Varying Delays - Jie Qi; Yuangong Sun (Discrete Dynamics in Nature and Society)
We study the exponential stabilizability for a class of switched nonlinear systems with mixed time-varying delays. By using a new technique developed for positive systems, we design the average dwell time switching under which the switched nonlinear system is exponentially stable for any bounded delays. Finally, numerical examples are worked out to illustrate the main theoretical result.